Training as a social purpose: are economic and social benefits delivered?. (9th August 2016) - Butler, Allan; Lobley, Matt
Abstract : This paper reports original research which measures the social and economic impact of training and skills development on individuals who participated in training provided by social purpose, nonprofit organizations. An implicit policy assumption is that such organizations contribute to social and economic regeneration. Examining the costs and benefits of training to trainees, an adapted Return on Investment methodology measures any economic benefit, while an Index of Social Benefit measures changes in individual well‐being. The results demonstrate that while changes to both the economic and social well‐being of trainees occur, it does not necessarily relate solely to the training they received. Instead, changes reflect other, often complex, aspects of trainees' lives, although training may facilitate change. Furthermore, social purpose, nonprofit organizations need to evince the socioeconomic benefits of their training programmes to secure future funding, public or private, but proving their successful delivery may be difficult to determine.